2021
DOI: 10.3390/pathogens10060662
|View full text |Cite
|
Sign up to set email alerts
|

Culture of Mycobacterium smegmatis in Different Carbon Sources to Induce In Vitro Cholesterol Consumption Leads to Alterations in the Host Cells after Infection: A Macrophage Proteomics Analysis

Abstract: During tuberculosis, Mycobacterium uses host macrophage cholesterol as a carbon and energy source. To mimic these conditions, Mycobacterium smegmatis can be cultured in minimal medium (MM) to induce cholesterol consumption in vitro. During cultivation, M. smegmatis consumes MM cholesterol and changes the accumulation of cell wall compounds, such as PIMs, LM, and LAM, which plays an important role in its pathogenicity. These changes lead to cell surface hydrophobicity modifications and H2O2 susceptibility. Furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 58 publications
1
1
0
Order By: Relevance
“…Taken together, our results would indicate that our mutant strain, while in the presence of high ROS levels, may modulate the intracellular redox balance and survive longer inside macrophages. This agrees with a recent report carried out by de Lima et al. (2021) where it was found that M. smegmatis grown in cholesterol persists intracellularly for a longer time causing less damage than when it grows in dextrose or glycerol.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Taken together, our results would indicate that our mutant strain, while in the presence of high ROS levels, may modulate the intracellular redox balance and survive longer inside macrophages. This agrees with a recent report carried out by de Lima et al. (2021) where it was found that M. smegmatis grown in cholesterol persists intracellularly for a longer time causing less damage than when it grows in dextrose or glycerol.…”
Section: Discussionsupporting
confidence: 93%
“…de Lima et al (2021) where it was found that M. smegmatis grown in cholesterol persists intracellularly for a longer time causing less damage than when it grows in dextrose or glycerol. Our data also reveal that, after growing in a lipid mixture, the infection of THP-1 macrophages by M. bovis BCG strains (wildtype and mutant) somehow results in a modulation of the immune response to facilitate their survival inside the host.…”
Section: Mtbcg Cultured In Lipids Induced Less Cytotoxic Damage Of Th...mentioning
confidence: 99%
“…Another important host-associated carbon source is cholesterol. In recent years, several groups have investigated metabolic and transcriptional changes induced by cholesterol, since fatty acids and cholesterol are proposed to act as major carbon and energy sources for Mtb in vivo, especially at later stages of infection [21][22][23]. Glycerol and Tween 80 were each applied as both molecules are traditionally used in mycobacterial culture and drug screening assays to promote growth.…”
Section: Introductionmentioning
confidence: 99%